THE INFLUENCE OF ISLAMIC BOARDING SCHOOL ENVIRONMENT AND TA’LIM MUTA’ALIM ON MORALS TOWARDS TEACHERS: THE ROLE OF SELF-AWARENESS - Nurhidayah, Litha Kurnia; Choiri, Moh Miftachul (Abjadia : International Journal of Education, 2024)
This study investigates the influence of the Islamic boarding school (pesantren) environment and Ta'lim Muta'alim studies on students' moral behavior towards teachers, with a focus on the mediating role of self-awareness. Grounded in the principles of Islamic education, the study addresses the critical issue of declining moral respect towards teachers in educational institutions. Using a quantitative research design, data were collected from 110 students of Jannaturroichan Islamic Boarding School in Jombang. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the relationships between variables. The results revealed that both the pesantren environment and Ta'lim Muta'alim studies significantly enhance students' moral conduct towards teachers, and self-awareness acts as a crucial mediator in strengthening this relationship. The findings highlight the novelty of integrating self-awareness as a core component in Islamic moral education to foster deeper respect for teachers. Based on these results, it is recommended that pesantren incorporate structured self-awareness training programs to cultivate positive student-teacher interactions and reinforce moral values within the educational framework of Islamic boarding schools.